Stochastic financial models - Kennedy, Douglas (Chapman & Hall/CRC financial mathematics series, 2010)
Offers a hands-on introduction to mathematical finance. This title includes the relevant mathematical background as well as many exercises with solutions. It presents the classical topics of utility and the mean-variance approach to portfolio choice